Organizational Management and Public Speaking Training for Student Organization Managers PGRI 1 Junior High School, Buduran, Sidoarjo - Taufikurrahman Taufikurrahman; Juwito Juwito; Farikha Rahmawati; Zainal Abidin Achmad (Nusantara Science and Technology Proceedings, 2022)
This community service activity can provide a breakthrough for PGRI 1 Junior High School (SMP PGRI 1) Buduran to produce (1) recommendations on the importance of providing organizational management briefing to students who become student organization administrators (OSIS) and Scouts, (2) organizational management training modules and public speaking for junior high school students. (3) Student organizations can adapt to changes in information technology so as not to be left behind by their competitors in social and academic fields. The role of leadership is needed to overcome change and maintain and develop the organization's existence. Communication activities in junior high school student organizations aim to establish mutual understanding and equate experiences among members of the organization to create the progress of human resources of the nation's young generation.